STRUGGLE FOR FREEDOM OF MADELEINE IN DANIELLE STEEL'S JOURNEY: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - SUPRAPTI, SRI (2010)
This research paper elaborates the struggle for freedom of Madeleine in Danielle steel's Journey that are analyzed through individual psychological approach. The objectives of the research are to analyze the structural elements of the novel and to analyze the novel based on individual psychological approach. This research belongs to a descriptive qualitative research. The object of the study is Danielle Steel's Journey published in 2000 in New York by Bantam Dell. The data sources are divided into, namely primary data source and secondary data source. The primary data source is the novel entitled Journey. Whereas the data source comes from both primary data source which is the novel itself and secondary data source are the other sources related to the analysis such as the author's biography, websites and other sources which are related to this study. Based on the analysis toward the novel, the writer concludes that the struggle of Madeleine against her freedom as a woman are shown by the structural elements which build the novel such as characters, setting, plot, theme, and point of view and from the individual aspects. The writer also finds that the major character more brevity to get her freedom in her life after she joint on a woman organizasition. Here, she realize that has ability and power to get her freedom in her life from abusing, both of physically and psychologically abuse.